Progress on physical methods for blood coagulation detection - Tang Yun; Zhu Jiang; Zhang Yuxian; Zhang Fan (Dianzi Jishu Yingyong, 2023)
Abstract： The assessment of coagulation can help diagnose blood diseases, guide treatment of cardiovascular diseases, and assess risk of bleeding during surgery. Physical coagulation testing is of great interest to clinical medicine because of its short detection time, high sensitivity, and simple operation. With the rapid development of optical coherence tomography (OCT) technology, it has been used in the blood coagulation detection. In this paper, we summarize the physical methods for the blood coagulation detection in recent years and specially review the applications of the OCT methods in the coagulation testing. The future development of blood coagulation detection is also prospected.